Efficacy and tolerability of add‐on lacosamide in children with Lennox‐Gastaut syndrome. (30th January 2014) - Grosso, S.; Coppola, G.; Cusmai, R.; Parisi, P.; Spalice, A.; Foligno, S.; Verrotti, A.; Balestri, P.
<x xml:space="preserve">Abstract</x> Objective Available data on the efficacy of lacosamide in children with Lennox‐Gastaut syndrome (LGS) are scarce and controversial. We present our experience with lacosamide therapy in children affected by LGS. Material and Methods Medical charts of all children affected by LGS receiving oral lacosamide adjunctive therapy in six paediatric neurology centres were retrospectively evaluated. Efficacy was determined according to the frequency of countable seizures during the 4 weeks prior to treatment and the frequency in the last 4 weeks of observation. Patients whose seizure frequency was reduced by at least 50% were defined as responders. Results Eighteen children (mean age 12.3 years) were identified. After a mean follow‐up period of 9 months, 33% of patients were responders. None of them was seizure‐free during the study period. The overall seizure reduction rate was 29%. The percentage reductions from baseline in tonic seizures and drop‐attacks rates were 31% and 20%, respectively. Adverse reactions occurred in 44% of patients. The drug was discontinued in four (22%) patients because of increased seizure frequency (three cases) and walking instability (another patient). Conclusions A third of children with LGS were responders after lacosamide adjunctive therapy. Although caution is still necessary when the drug is used in children with LGS, our preliminary observations suggest that lacosamide might be effective and represent a possible therapeutic option in children affected by LGS.